Green Development Rights For Optimizing Urban Area And Coastal Areas In Indonesia (Consitency Of The State Of The Doctrine Of The Right To Control The State) - I Gusti Ayu Ketut Rachmi Handayani (The Constitutional Court of the Republic of Indonesia, 2016)
The green development right paradigm will elaborate the ontology (nature), and the ways or methods in order to achieve the ultimate goal of the green development right. This ultimate goal will be focused on the creation of the ideal maritime systems that may guarantee all related parties, such as individual, society, or community, private sectors and the government, to convert their potentials to be functional towards public welfare. The core elements of the green development right will emphasizes the series of norms in managing the coastal and frontline island potentials. The normative framework covers Environmental Law, Fishery Law, and Coastal Law. The research methods use an empirical approach and normative approach. The study documents the analysis consists of constitutions, legislation and various policies relating to the subject matter studied in Indonesia area and the problems it faces and report the results of the various meetings, seminars, public hearings.